Biological Functions of Strigolactones and Their Crosstalk With Other Phytohormones - Wu, Fenghui; Gao, Yinping; Yang, Wenjing; Sui, Na; Zhu, Jianping (Frontiers in Plant Science, 2022)
Phytohormones are small chemicals critical for plant development and adaptation to a changing environment. Strigolactones (SLs), carotenoid-derived small signalling molecules and a class of phytohormones, regulate multiple developmental processes and respond to diverse environmental signals. SLs also coordinate adjustments in the balance of resource distribution by strategic modification of the plant development, allowing plants to adapt to nutrient deficiency. Instead of operating independently, SL interplays with abscisic acid, cytokinin, auxin, ethylene, and some other plant phytohormones, forming elaborate signalling networks. Hormone signalling crosstalk in plant development and environmental response may occur in a fully concerted manner or as a cascade of sequential events. In many cases, the exact underlying mechanism is unclear because of the different effects of phytohormones and varying backgrounds of their actions. In this review, we systematically summarise the synthesis, signal transduction, and biological functions of SLs and further highlight the significance of crosstalk between SLs and other phytohormones during plant development and resistance to ever-changing environments.